PENERAPAN BUSINESS INTELLIGENCE SYSTEM PADA TRANSAKSI AGEN BRILINK FIANCELLULER - Sabilla, Alzena Dona; Yoga, Hendra Tri; Saputro, Heru (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Fiancelluler brilink agent is a business engaged in the service sector. The services offered by brilink fiancelluler agents are serving money transfers, cash withdrawals and multipayment payments. This study aims to apply business intelligence to the transaction information system for brilink fiancelluler agents which is implemented in the form of reporting dashboards as a reference for decision making at brilink fiancelluler agents. The method used is FAST (Framework for the Application System Thinking). With stages: scope definition, problem analysis, requirements analysis, logical design and physical design. The results of this study are in the form of a reporting dashboard that contains information about transactions at brilink fiancelluler agents in the form of completed transactions, transaction graphs, transaction details, transaction types, frequently used banks and gender. Testing on the fiancelluler brilink agent system uses 2 methods. First testing with the black box method with 8 tests with no results found errors or the system works according to orders. Both usability methods with 4 aspects of testing namely learnability, flexibility, effectiveness, attitude with 40 respondents. The results obtained from the usability testing method are 84.22% very suitable for use by consumers